Multi-Omics on Traditional Medicinal Plant of the Genus Aconitum: Current Progress and Prospect - Ting Wang; Cai Rangji; Wenbin Liu; Jing Ma; Ruichen Zhou; Liang Leng; Yi Zhang (Molecules)
Aconitum stands out among the Ranunculaceae family for its notable use as an ornamental and medicinal plant. Diterpenoid alkaloids (DAs), the characteristic compounds of Aconitum, have been found to have effective analgesic and anti-inflammatory effects. Despite their medicinal potential, the toxicity of most DAs restricts the direct use of Aconitum in traditional medicine, necessitating complex processing before use. The use of high-throughput omics allows for the investigation of Aconitum plant genetics, gene regulation, metabolic pathways, and growth and development. We have collected comprehensive information on the omics studies of Aconitum medicinal plants, encompassing genomics, transcriptomics, metabolomics, proteomics, and microbiomics, from internationally recognized electronic scientific databases such as Web of Science, PubMed, and CNKI. In light of this, we identified research gaps and proposed potential areas and key objectives for Aconitum omics research, aiming to establish a framework for quality improvement, molecular breeding, and a deeper understanding of specialized metabolite production in Aconitum plants.